A evolução do mercado de crédito para empresas no Brasil: causalidade crédito X atividade econômica - Sucupira, Aldenira Lima Leandro (2022)
The study of the credit market is of great importance for the economy of a country, since, from it, financing strategies can be drawn up aimed at household consumption, or at certain productive sectors. The expansion of the offer of credit for Companies enables the growth of Economic Activity, with the companies' short and medium-term cash needs met. The main contribution of this Dissertation is to analyze how loans affect economic activity. To obtain these results, causality tests were performed for panel data as proposed by Granger (1969) and Dumitrescu-Hurlin (2012). The Brazilian Economic Activity Index - IBC and the Credit Portfolio Balance (Total, Individuals and Companies), released by the Central Bank, from Jan/18 to Aug/22 were used as variables. Our sample considers 13 States of the Federation. The analysis showed the following results, at 5% significance: the increase in the balance of the PJ loan portfolio causes an increase in the Economic Activity Index, just as the increase in the economic activity index reflects positively on the growth of the loan portfolio balance PJ. Regarding credit directed to individuals, the study showed that the increase in the balance of the credit portfolio for the individual segment does not cause, in Granger's sense, an increase in the Economic Activity Index for the States analyzed, as well as the Elevation of the Economic Activity Index does not cause growth in the balance of the credit portfolio for the individual segment, however, the absence of causality between the growth of the Individual Credit Portfolio Balance and the Economic Activity Index did not occur homogeneously. Finally, when analyzing the causality between Total Credit and Economic Activity, the test reveals that the increase in the Total Credit Portfolio Balance does not cause, in Granger's sense, the increase in the Economic Activity Index, and in the inverse relation, the increase of the Economic Activity Index does not cause, in Granger's sense, the increase in the Total loan portfolio Balance.